Correlation of Prior Experience and Self-Efficacy with the Action Awareness of Scabies Prevention - Ardhiles Wahyu Kurniawan; Wiwit Dwi Nurbadriyah; Shinta Wahyusari; Apriyani Puji Hastuti (STIKes Patria Husada Blitar, 2026)
Scabies prevention faces significant behavioral challenges, where self-efficacy and prior experiences play crucial roles in influencing individual awareness. This study aims to evaluate the relationship between prior experiences and self-efficacy with action awareness in scabies prevention within Islamic boarding schools (pesantren). The study employed a correlational cross-sectional design involving a population of 213 Islamic boarding administrators from eight pesantren in Malang Regency. A total of 140 respondents were selected using proportional random sampling to ensure proportional representation. Data analysis was conducted using Somers’d and Gamma statistical tests. The results revealed a significant relationship between prior experiences and action awareness (p = 0.002) with a moderate negative correlation (R = -0.459), indicating that negative experiences are associated with lower levels of action awareness. Furthermore, a highly significant relationship was found between self-efficacy and action awareness (p = 0.000) with a very strong positive correlation (R = 0.867), demonstrating that higher self-efficacy is associated with increased action awareness. These findings highlight the importance of positive experiences and enhancing self-efficacy in fostering better scabies prevention behaviors in Islamic Boarding School settings.